Driving factors of variation in fertilizer nitrogen recovery efficiency in maize cropping systems across China and its microbial mechanism - Xiao, Xun; Wang, Yuekai; Dai, Wentai; Liu, Kailou; Jiang, Fahui; Xie, Zubin; Shen, Ren Fang; Zhao, Xue Qiang (Geoderma, 2024)
•Fertilizer N recovery efficiency (FNRE) in maize varies among different soils.•Soil pH and organic matter drive variations in maize FNRE.•Optimal soil pH for maize FNRE is around 6.50–6.62.•Optimal soil organic matter for maize FNRE is around 35.25–46.90 g kg−1.•Soil dissimilatory nitrate reduction to ammonium contributes to maize FNRE. Maize (Zea mays L.) fertilizer nitrogen (N) recovery efficiency (FNRE) shows regional differences in China, and is more strongly affected by soil properties than by climate. However, how soil factors regulate maize FNRE is poorly understood. Herein, 15N tracer pot experiments combined with absolute microbial quantification sequencing were conducted using eight soils covering the main maize cropping systems from northern to southern China. The aim was to elucidate which soil factors affect maize FNRE and identify their optimal range for maximizing FNRE while minimizing N loss. Our results show that soil pH, soil organic matter (SOM), and clay and sand contents were the key factors affecting maize biomass and FNRE across the eight tested soils. Maize biomass and FNRE had parabolic relationships with soil pH, SOM, clay, and sand contents, whereas N loss displayed the opposite trend. The highest maize biomass and FNRE and lowest fertilizer N loss were in the soils with pH of 6.50–6.62, SOM level of 35.25–46.90 g kg−1, clay content of 41.12 %–44.42 %, and sand content of 17.71 %–23.41 %. Under these soil conditions, maize growth and soil N retention capabilities exhibited a high degree of coordination. Bacterial communities differed significantly among the soils, sharing the same soil drivers as maize biomass and FNRE. The abundance of N cycling genes (nasA, narI, narJ, nrfA, and nrfB) involved in dissimilatory nitrate reduction to ammonium (DNRA) was positively correlated with FNRE and negatively correlated with fertilizer N loss, suggesting that DNRA may contribute to soil N retention and enhance FNRE by affecting substrates for nitrification and denitrification. Our study demonstrates that soil pH, SOM, and texture are three key factors driving FNRE variation in maize cropping systems across China, and high microbial-driven DNRA may account for maximum maize FNRE. These findings highlight the importance of tailored FNRE enhancement strategies based on soil characteristics.